Long‐term safety of unopposed estrogen used by women surviving myocardial infarction: 14‐year follow‐up of the ESPRIT randomised controlled trial. (18th February 2014) - Cherry, N; McNamee, R; Heagerty, A; Kitchener, H; Hannaford, P
<x xml:space="preserve">Abstract</x> Objective To compare health outcomes during 14‐year observational follow‐up in women initially randomised to unopposed estrogen or placebo. Design At recruitment to the Estrogen for the Prevention of Re‐Infarction Trial (ESPRIT) women were assigned to estradiol valerate: 2 mg or placebo treatment for 2 years. Setting Women were recruited from 35 hospitals in the northwest of England and Wales in July 1996–February 2000. Sample Women aged 50–69 surviving their first myocardial infarction. Methods All women were followed by data linkage to UK mortality and cancer records; mean follow‐up 14.1 and 12.6 years, respectively. In an intention‐to‐treat analysis, hazard ratios (HRs) were computed, overall and stratified by age at recruitment. Outcome measures Death (all‐cause, cardiac disease, stroke or cancer) and cancer incidence (any, breast or endometrium). Results There were 418 deaths in 1017 women randomised. The all‐cause mortality HR of 1.07 (95% CI 0.88–1.29) indicated no significant difference between treatment groups. Women aged 50–59 years at recruitment had lower HRs than women aged 60–69 years for all outcomes except ischaemic heart disease. Among 149 incident cancers there were seven cases of breast cancer in the intervention arm and 15 in the placebo; HR 0.47 (95% CI 0.19–1.15). There were no deaths from endometrial cancer but three incident cases, one in the active arm and two in placebo. Conclusions These results suggest that unopposed estrogen may be used safely by women with an intact uterus surviving a first myocardial infarction.